2009
DOI: 10.1128/cvi.00037-09
|View full text |Cite
|
Sign up to set email alerts
|

The Fcγ Receptor IIA-R/R131 Genotype Is Associated with Severe Sepsis in Community-Acquired Pneumonia

Abstract: Community-acquired pneumonia (CAP) can be caused by a variety of microorganisms but is most frequently associated with Streptococcus pneumoniae and gram-negative bacteria like Haemophilus influenzae. Encapsulated bacteria are able to escape phagocytosis, unless they are bound by immunoglobulin G2 subclass antibodies. These antibodies interact with Fc␥ receptor IIa (Fc␥-RIIa), thereby facilitating opsonophagocytosis of the encapsulated bacteria. We studied the relationship between the Fc␥-RIIa-R/H131 polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 19 publications
2
27
0
2
Order By: Relevance
“…The Fc␥RIIa-H131 allotype has higher binding efficiency for IgG2 and greater phagocytic capability for IgG2-opsonized bacteria than the Fc␥RIIa-R131 allotype. A recent study by Endeman et al showed that the Fc␥RIIa-R131R genotype was found more frequently in patients with severe community-acquired pneumonia caused by S. pneumoniae and H. influenzae (5). In our patients with bacterial coinfections, this association was not obvious (Table 3).…”
Section: Discussionmentioning
confidence: 49%
“…The Fc␥RIIa-H131 allotype has higher binding efficiency for IgG2 and greater phagocytic capability for IgG2-opsonized bacteria than the Fc␥RIIa-R131 allotype. A recent study by Endeman et al showed that the Fc␥RIIa-R131R genotype was found more frequently in patients with severe community-acquired pneumonia caused by S. pneumoniae and H. influenzae (5). In our patients with bacterial coinfections, this association was not obvious (Table 3).…”
Section: Discussionmentioning
confidence: 49%
“…For example, the low affinity variant of FcγRIIa (R131) confers increased susceptibility to severe bacterial infections and sepsis, likely due to impaired microbial clearance (37, 103, 104). In contrast, in dengue infection, where antibody-mediated enhancement (ADE) of virus infectivity can occur, this low binding FcγRIIa polymorphism is associated with asymptomatic infection and improved clinical outcomes (105, 106).…”
Section: Signaling and Function Of Anti-tumor Antibodiesmentioning
confidence: 99%
“…[4] Our results also suggest that immune cells in patients' HI express different levels of ICAM-1 and therefore ICAM-1 during the formation of HI may be involved in the adhesion, capture, immune adjustment, and phagocytosis between immune cells and pathology hematopoietic cells.…”
Section: Discussionmentioning
confidence: 77%
“…So it plays an important biological role in killing intracellular pathogen. [4,12] Immunofluorescence staining showed that immune cells in three types of HI all secreted IL-12 which was closely related with elevated serum IL-12 levels. Meanwhile, in patients with AIRH CD19 + B lymphocytes and CD3 + CD8 + lymphocytes were significantly increased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation